Aktivitas Antioksidan Kulit Pisang Muli (Musa acuminata linn) dan Kulit Pisang Kepok (Musa paradisiaca formatypica) - Yulis, Putri Ade Rahma; Sari, Yelfira (Al-Kimia, 2020)
This study examined the content of banana peel. The research began with an extraction process then continued with phytochemical tests. Qualitatively result showed banana peel contain quite complex secondary metabolites including flavonoids, saponins, phenolics, tannins, steroids and triterpenoids for Muli banana peels and flavonoids, saponins, phenolics, tannins, and triterpenoids for Kepok banana peels. Qualitative tests were conducted to detect total phenolic and flavonoid content using Microplate Reader. Flavonoids averaged 19.797 mg QE / g for Muli banana peel and for Kepok banana peel 15, 529 mg QE / g. The measurement results of the total phenolic content of Muli banana peel was 108.336 mg GAE / g and for Kepok banana 32, 496 mg GAE / g. Antioxidant activity for Muli banana peels has an IC50 value of 27, 56 µg / ml which means it belongs to a group with high antioxidant activity and Kepok banana 479.77 µg / ml which is classified as a low antioxidant activity but still within the range of potential values as antioxidant. From this research, it is known that both of types banana peels have the potential as raw material for developing products with high antioxidant levels Keywords: Banana peels, antioxidants, secondary metabolites